Unveiling the risks of low birth weight prevalence: An ecological study in West Java - Jihan Alfira; Yayuk Farida Baliwati; Hadi Riyadi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Low birth weight (LBW) is a problem that encompasses the entire life cycle. Children born with low birth weight are highly vulnerable to developing diseases and death, and remain undernourished. This study aimed to analyze the factors related to the prevalence of LBW in West Java Province. This ecological study utilized secondary data from 2022 obtained from the Ministry of Health, Social Office Central Bureau of Statistics, and National Food Agency. The unit of analysis was all districts in West Java. The dependent variable was the prevalence of LBWs. The independent variables were pregnancy age at risk, preterm birth, MUAC <23,5 cm, parity, food security, early marriage, maternal education, and poverty. Pearson and Spearman correlation tests were conducted to examine the relationship between each independent variable and the prevalence of LBW. The overall prevalence of LBW infants was 20,9%, with a significant positive association found between the pregnancy age at risk percentage, percentage of preterm birth, percentage of MUAC <23,5 cm, percentage parity at risk, food security score, percentage of low education, and percentage of poverty (p=0,046, p=0,025, p=0,039, p=0,042, and 0,044; p=0,002). In conclusion, the percentage of preterm births is the primary cause of low birth weight in West Java